Kristologi Eskatologis: Kerajaan Seribu Tahun Dalam Pemikiran Teologi Kristen - Dedi Surianto Laia; Aprianus Lendrik Moimau (Jurnal Magistra, 2024)
This article discusses the concept of Eschatological Christology, especially in the context of Christian theological thought, with a focus on the idea of the Millennial Kingdom. The author explores the theological interpretations of the future found in Christian scripture, particularly in relation to Christ's return and His thousand-year reign. The discussion includes various different theological perspectives, so this article summarizes views about the millennial kingdom (millennium kingdom) using qualitative methods, namely by using existing literature data.